The Theory of Vital Space - Theoretical Study of Geopolitical Dimensions, Targets and Means (USA) Case Study (Journal of the College of Education for Women, 2019)
The concept of forming the living space in the American strategic thought has animportant position it is regarded as an strategic movement that it supports the AmericanUnited States with the huge capabilities in its own concern that enables it to approach ofAmerican administration , we find that of different historical periods it works to establish thatthe geopolitical dimension which is accompanied with the ability of American response forthe evens that in its own turn enables the American united states to seize the growing chancesin the global strategic environment This study includes five chapters :- Chapter one: The idea of living space.- Chapter two: Geopolitical dimension of living space theory.- Chapter three: The motives of living space theory.- Chapter Four: The machines of living space theory achievement.- Chapter Five: The employment of living space in American rational security.المقدم